Integration of Mobile Learning Technologies in Afghanistan Universities: Opportunities and Challenges - Tamanna Quraishi; Bayani, Bibi Marwa; Samira Yashar; Mehriya Daudzai; Rohina Salamzada; Masooma Amini; Musawer Hakimi (Education Specialist, 2024)
This study investigates the adoption and integration of mobile learning technologies in Afghanistan universities, aiming to assess the current status, challenges, opportunities, and perceptions surrounding mobile learning initiatives in these institutions. The research employed a quantitative approach, utilizing surveys distributed via Google Forms to gather data from stakeholders. A sample size of 200 students and educators across various disciplines and geographical locations within Afghanistan universities was utilized. The results section presents various findings, including gender distribution among students, reliability and validity measures of study aspects, adoption rates of mobile learning technologies, perception of infrastructure availability, extent of existing initiatives, integration into the curriculum, satisfaction with accessibility, and perception of effectiveness and accessibility. Noteworthy results include equitable gender representation in enrollment, robust reliability and validity measures, higher adoption rates of mobile learning technologies among female respondents, positive perceptions of infrastructure availability and existing initiatives, moderate integration into the curriculum, and generally satisfactory accessibility. However, disparities exist in the perception of effectiveness and accessibility between genders, highlighting areas for improvement. In conclusion, the study provides valuable insights into the current landscape of mobile learning in Afghan public universities, underscoring the importance of addressing gender disparities and technological barriers to further enhance educational outcomes. Recommendations for future research and implications for stakeholders are discussed, emphasizing the need for gender-sensitive approaches and targeted interventions to maximize the potential of mobile learning technologies in advancing higher education in Afghanistan.